Attribution Patterns in Men Who Ejaculate Before They Desire: An Internet Survey. Issue 5 (3rd July 2016) - Rowland, David L.; Mikolajczyk, Laura C.; Pinkston, Devin M.; Reed, Holly M.; Lo, Darren M.
Abstract : Men with erectile problems tend to attribute negative sexual experiences to themselves, in contrast with sexually functional individuals who tend to attribute negative experiences to external factors such as the circumstance or relationship. In this study, we investigated attribution patterns in men with premature ejaculation (PE) symptoms—a group not yet investigated in this regard—to determine whether they follow patterns similar to men with erectile problems. Using an Internet-based approach, we compared attribution responses of 289 men with PE symptoms with 433 sexually functional men on a series of five sexual scenarios (two presenting a positive experience and three presenting a negative experience). Men with PE symptoms were more likely to take blame for any negative sexual experience, including ones unrelated to ejaculating quickly, whereas functional men were more likely to attribute blame to the partner, circumstance, or relationship. Men with PE symptoms also took less credit for positive sexual experiences than functional counterparts, attributing them to the partner or circumstance. These results point out similarities across men with a variety of sexual problems, but also raise questions regarding differences between men with erectile problems and men with problems of ejaculating before desired. Several therapeutic strategies are offered.